(untitled) (National Administration Journal, 2019)
By means of economic and environmental indicators, an analysis was made as to whether Costa Rica’s economic growth model is or not linked to greenhouse gas emissions. To this effect open database information was collected for the years between 1990 and 2014. According to a logistic regression model, the results revealed that the growth of the gross domestic product and the use of energy in kilogram oil equivalent are significant predictor variables for the variable dependent on the total emission of greenhouse gases. In an occasional analysis from 2008 to 2014, a disconnection was observed, but the analysis must continue until 2018 based on a new national inventory of greenhouse gases. It was concluded that Costa Rica’s growth is historically linked to the total emission of greenhouse gases, which limits a model of green growth.